Efficacy Of N-Acetylcysteine In Non- Acetaminophen Acute Liver Failure. - Rukh, Mah; Jabbar, Asjid; Shaikh, Yasmin; Azeem, Abdul; Aslam, Ahsan; Usmani, Sauda (Journal of Neonatal Surgery, 2025)
Introduction: Acute liver failure (ALF) is a relatively rare, but severe, life-endangering medical emergency. To date, there is no established treatment for non-acetaminophen-induced acute liver failure (NAI-ALF) other than liver transplantation, and little is known about the use of N- acetylcysteine (NAC) in NAI-ALF. Objective: To determine the efficacy of acetylcysteine in non-acetaminophen acute liver failure. Study Design: Descriptive case series. Setting: Department of Medicine, Mayo Hospital, Lahore. Duration of Study: Study was carried out over a period of six months from 03-10-2021 to 03- 04-2022. Material and Methods: Total 81 patients presented to the Department of Medicine, Mayo Hospital, Lahore, fulfilling the Inclusion criteria were selected. Informed consent was taken from each patient. All patients were given intravenous N-acetylcysteine (150mg/kg in 5% dextrose in 15 mins followed by 50mg/kg over 4 hours then 100mg/kg over 16 hours) for duration of 72 hours. All patients were followed by the researcher for 4 weeks and efficacy and analyzed in SPSS version 25.0 and presented as frequency and percentages. Results: Total of 81 patients were included in the study, there were 66.7 %(n=54) were in age group of 20-40 years and 33.3% (n=27) were in age group of 41-70 years and mean age was calculated as 737.93±11.09 years. Gender distribution of the patients was done, it showed that 44.4 %(n=36) were male whereas 55.6% (n=45) were females. Percentage of efficacy of acetylcysteine in non- acetaminophen acute liver failure was 30.9%(n=25). Conclusion: We concluded that in patients with non-acetaminophen-related acute liver failure, acetylcysteine significantly improves overall survival